UGC NET/SET PAPER I - Surender Singh (Chennai McGraw Hill Education, 2017)
UGC NET/SET Paper I is a comprehensive text, with detailed coverage of all topics in the UGC NET/SET Paper I examinations conducted by the University Grants Commission to test the eligibility of candidates for prospective academic roles in various government and government-aided colleges. Written by eminent academics and subject experts who have several books on topics like Communication, Information Technology, Geography, Numerical Aptitude, Research Aptitude and Teaching Aptitude, to their credit, the book is of immense importance to all aspirants of NET/SET eligibility examinations
1. Complete revision and addition of content in every chapter in this edition 2. Divided into nine core sections, each written by an expert on the subject 3. Theoretical text extremely lucid and presented in concise and simple language 4. New questions to provide a plethora of multiple choice problems for practice 5. Inclusion of five Model Test Papers 6. Previous Years' Papers provided with solutions from 2009 to June, 2016